A Novel Acellular Dermal Scaffold Prepared Using High-Intensity Focused Ultrasound Energy for the Repair of Soft Tissue Defects - Abdul-Monem, Mohamed M.; Helal, Mohamed H.; Aboushelib, Moustafa N. (European Dental Research and Biomaterials Journal, 2020)
Objective To evaluate a naturally derived acellular dermal scaffold for soft tissue reconstruction using high-intensity focused ultrasound energy (HIFU).Materials and Methods Acellular dermal scaffolds (ADSs) were prepared by purification of bovine skin. Half of the scaffolds were subjected to high-intensity focused ultrasound energy (HIFU) to modify collagen structure, whereas the other half was used as control. A large skin defect was made in the dorsum of white mice, and the scaffolds were used to cover the induced defects. Wound healing was evaluated histologically after 2, 6, and 12 weeks using common and specific stained sections (n = 20).Statistical Analysis Mean values and standard deviations were calculated for each group, and Student’s t-test was used for statistical analysis (α= 0.05; n = 20).Results After 2 weeks, all examined specimens revealed the presence of inflammatory cellular infiltration and early immature blood vessel formation. After 6 weeks, inflammatory cellular infiltration was reduced, with evidence of maturation of new blood vessels observed for all groups. After 12 weeks, there was a significant increase (F = 124, p < 0.01) in new collagen formation and count of mature blood vessels observed for the HIFU group compared with control. Evidence of remodeling of new collagen fibers and biodegradation of the grafts was also observed.Conclusions HIFU-modified ADSs enhanced wound healing and could be used to cover large soft tissue defects.
Keywords: HIFU; acellular dermal scaffold; collagen matrix; soft tissue repair